Plant response to fungal root endophytes varies by host genotype in the foundation species Spartina alterniflora. Issue 12 (30th November 2020) - Hughes, A. Randall; Moore, Althea F. P.; Gehring, Catherine
Abstract : PREMISE: Root‐associated fungi provide a wide range of functions for their host plants, including nutrient provisioning, pathogen protection, and stress alleviation. In so doing, they can markedly influence host‐plant structural and physiological traits, although the degree to which these effects vary within particular plant host species is not well understood. METHODS: We conducted a 7‐month common‐garden inoculation experiment to test the potential effects of a marine fungus ( Lulwoana sp.) on the phenotypic traits of different genotypes of the host, the salt marsh plant species Spartina alterniflora . Lulwoana belongs to the dark septate endophytes (DSE), a polyphyletic group of fungi that are commonly found colonizing healthy plant roots, though their ecological role remains unclear. RESULTS: We documented significant impacts of Lulwoana on S. alterniflora morphology, biomass, and biomass allocation. For most traits in our study, these impacts varied significantly in direction and/or magnitude across S. alterniflora genotypes. Effects that were consistent across genotype were generally negative. Plant response was not predicted by the percentage of roots colonized, consistent with findings that dark septate endophytes do not necessarily influence plant growth responses through direct contact with roots. CONCLUSIONS: The observed changes in stem height, biomass, and biomass allocation have important effects on plant competitive ability, growth, and fitness, suggesting that plant–fungal interactions have community and ecosystem level effects in salt marshes.